2000
DOI: 10.1088/0963-6625/9/1/301
|View full text |Cite
|
Sign up to set email alerts
|

Drought, debate, and uncertainty: measuring reporters' knowledge and ignorance about climate change

Abstract: Increasingly, the media are important sources of scientific information. Recent studies indicate that this is especially true for climate change. This study analyzes reporters' understanding of climate change by identifying sources of reporter knowledge about climate change, measuring reporters' acquired knowledge against the scientific consensus, and analyzing differences in reporter knowledge based on several factors that may influence climate change reporting. Results show that reporters who primarily use s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 16 publications
2
105
1
2
Order By: Relevance
“…Studies have shown that the mass media has been a primary source of climate news for the public (e.g., Brulle et al 2012;Nelkin 1995;Wilson 2000a), journalists (Wilson 2000b), and policymakers alike (Sundblad et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the mass media has been a primary source of climate news for the public (e.g., Brulle et al 2012;Nelkin 1995;Wilson 2000a), journalists (Wilson 2000b), and policymakers alike (Sundblad et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Graeme Pearman called the evidence facing the Toronto global conference of concerned scientists and bureaucrats a 'clarion call to politicians to take action' (Lowe 1989: 4 In the United States, media research has suggested the same phenomenon: media stories peaked between 1988 and the early 1990s, and scientists were a primary source of information during that early period. Environmental journalists recalled that media coverage picked up again around 1997, when the Kyoto Protocol was under discussion (Wilson 2000).…”
Section: : Coming To Grips With a Terrifying Global Experimentsmentioning
confidence: 99%
“…Science communication scholar Kris Wilson posed more than 70 questions about global climate change to members of the Society of Environmental Journalism, a group that accepts into 'active' membership only individuals who produce stories for mass media outlets that serve the public (Wilson, 2000). He then explored predictors of knowledge levels, among them whether the respondent had majored in an 'environmental science' and the percent of time the respondent devoted to covering environmental issues.…”
Section: Where's the Evidence?mentioning
confidence: 99%